Solidarity in Ethnically Diverse Contexts: Supportive Relations of First‐Generation Roma Graduates’ Social Mobility in Hungary - Judit Durst; Margit Feischmidt; Zsanna Nyírő (Social Inclusion)
The relationship between Roma and non‐Roma in Central and Eastern European countries is determined by growing socio‐economic inequalities, racism based on structural inequalities, and far‐right policies of scapegoating. This trend is reinforced by the generally low level of social mobility. However, parallel to the main trend, a less visible process enables the social mobility of people of Roma origin born into marginalised, socio‐economically low‐status families. In this article, we aim to link issues of solidarity and diversity by exploring the support networks of educational and social mobility trajectories of Roma in Hungary. Based on 102 narrative life‐story interviews with first‐generation Roma graduates, we explore the helping and hindering relations, as well as the solidarity dynamics, that enabled their social mobility through education. The article answers the following questions: What types of supportive relations facilitate upward social mobility? What kind of mobility trajectories do these supportive (and hindering) relations engender? What happens to those who experience dislocation of social class and change of status? How do they navigate attachment to the community of origin and the attained middle class? By analysing narratives, we aim to highlight personal experiences of (educational) mobility and belonging by identifying different mobility trajectory ideal types and their accompanying supportive relations. Scholars of solidarity usually research the helpers. Here, we shift the perspective and research those lived experiences of solidarity that come from a racialised minority and receive help through their social mobility paths. Our research findings demonstrate that initial solidarity towards the vulnerable can have a spill‐over effect: The helped can become helpers. In our case, first‐generation Roma professionals who have first‐hand experience with social and economic inequalities become drivers of social change, partly by building bridges across communities, partly by fulfilling jobs in the mainstream economy, and also by creating new narratives and advocating for social justice.